Durability Study on the Red mud-based Ternary Blended Geopolymer Concrete - Chakrapani, Eti T; Ramesh, Kode V; Potharaju, M (Technium EcoGeoMarine, 2022)
Concrete made with geopolymer technology is thought to be both pro-ecological and minimal cost-effective. Geopolymer concrete manufacture aids in the conversion of industrial by-product materials into reusable products. Geopolymer concrete outperforms OPC concrete in terms of strength. The ternary blended high-molarities (12M) geopolymer concrete used in this experiment was made of red mud (RM), fly ash (FA), and Ground granulated blast furnace slag (GGBFS). The current study intended to establish the best ratio of RM - FA - GGBFS -based ternary geopolymer concrete. The compressive strength, split tensile strength, and flexural strength tests were performed to determine the strength properties and water absorption, permeability, and sorptivity tests determined the durability characteristics. The results showes that the proportions of RM-based ternary GPC with RM: FA:GGBFS in 45:35:20 ratio resulted in a significant increase in the synthesis. This resulting in improved mechanical and microstructural properties than the other proportions. Higher results were also seen at the aforementioned ratio in the chemical analysis performed on the ternary-based geopolymer paste to determine the maximum pH value. The study’s findings are encouraging sustainable and cost-effective routes for dealing with the industrial by-products that are presently produced in multiple regions.